The past and future of UK health spending - George Stoye; Max Warner; Ben Zaranko (Institute for Fiscal Studies (IFS), 2024)
Health spending, and the performance of the NHS, will feature prominently in the upcoming general election campaign. Many different factors matter for NHS performance and for the wider health of the population, but one important factor is the level of spending on health services. In this IFS pre-election briefing, we examine UK government health spending over the past seven decades. We then discuss the outlook for health spending over the years to come.
Keywords: 330; Government finances and spending; Health and social care; Government spending; Health; Healthcare; NHS; Public finance; Public sector